Processing tress on farms : - Hanson, Ian (RIRDC, 1997)
Australia has a trade deficit in its forestry products industry with items imported being of higher value than those exported. These products come mainly from native and plantation forests. It is widely accepted that increased farm forestry activity over the last two decades has provided numerous environmental benefits, such as soil protection from wind and water erosion, salinity control and improved water quality.